Individual factors in the relationship between stress and resilience in mental health psychology practitioners during the COVID-19 pandemic. (September 2022) - Panourgia, Constantina; Wezyk, Agata; Ventouris, Annita; Comoretto, Amanda; Taylor, Zoe; Yankouskaya, Ala
Utilising an online survey, this study aimed to investigate the concurrent effects of pre-pandemic and COVID-19 stress on resilience in Mental Health Psychology Practitioners (MHPPs) ( n = 325), focussing on the mediation effects of specific individual factors. Optimism, burnout and secondary traumatic stress, but not coping strategies, self-efficacy, compassion satisfaction, or self-compassion, mediated both the relationship between pre-pandemic stress and resilience and COVID-19 stress and resilience. Increased job demands caused by the pandemic, the nature and duration of COVID-19 stress may explain this finding. Training and supervision practices can help MHPPs deal with job demands under circumstances of general and extreme stress.